Mental image reproductive static and kinetic in subjects with mild and moderate mental retardation - Rivera Benavides, José Carlos (2011)
In genetic psychology of J. Piaget, the mental image marks the beginning of representational figural cognitive functions (2-7 years) with B. Inhelder studied the breeding space images within which the most elementary are the static and kinetic. We assume that they are involved in executive intelligence. Here our intention to explore in subjects with mild to moderate mental retardation who do not reach the operative domain representation. For this purpose we apply the Scale Executive Borelli- Oléron, which the reformulated in terms of constructs of static and kinetic images. The results were that subjects with mild mental retardation yielded more static images and even more in the kinetics compared to the moderates.